PENGARUH HARGA DAN SUASANA CAFE TERHADAP KEPUASAN KONSUMEN (STUDI KASUS UNCLE SAM’S CAFE AND RESTO LUBUK PAKAM DELI SERDANG) - Mastriani, Agus; Wulandari, Sari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2021)
The results of the data of this study were found to have a positive and significant effect on price and cafe atmosphere on consumer satisfaction at Uncle Sam's Cafe and Resto Lubuk Pakam Deli Serdang. The data analysis technique used in this research is descriptive quantitative. The sample in this study were consumers at Uncle Sam's Cafe and Resto Lubuk Pakam Deli Serdang, amounting to 68 people. The results of this study obtained multiple linear regression equation Y = 6.863 + 0.242 X1 + 0.346 X2 + e. The constant value of 6.863 means that without the Price and Cafe Atmosphere variable, the Customer Satisfaction is 6.863, the Price variable is 0.242 and the Cafe Atmosphere variable is 0.346 indicating that every increase in the Price and Cafe Atmosphere, the Customer Satisfaction will increase by 0.242 for the Price Variable and for the Variable Cafe atmosphere is 0.346. Partial test results Price variable has a positive and significant effect on Consumer Satisfaction at Uncle Sam's Cafe and Resto Lubuk Pakam Deli Serdang, where the value of tcount > ttable (6.668 > 1.668) for the Price variable and for Variavel Suanasa Cafe the value of tcount > ttable (8.034 > t table 1.668) with a significant level of 0.000 <0.05, this shows Ho is rejected and Ha is accepted. Then the value of R square obtained is 0.856. This figure shows that 85.6.5% of customer satisfaction (the dependent variable) can be explained by the variables of Price and Cafe Atmosphere. it means that the percentage of Price and Cafe Atmosphere on Consumer Satisfaction is 85.6%, while the remaining 14.4% is influenced by other variables not examined by this study.